Psychological Momentum—A Key to Continued Success - Iso-Ahola, Seppo E.; Dotson, Charles O. (Frontiers in Psychology, 2016)
One of the most fundamental characteristics about humans is their desire for success, especially in highly competitive societies. What does it take to be successful? Is success simply a matter of better performance, and if so, what specifically is it about performance that determines success? A long research tradition suggests that psychological momentum (PM) plays a critical role in goal pursuit and achievement. Accordingly, sequential runs of success are an essential feature of high levels of performance, meaning that better performers perceive and experience momentum of success, ride it as long as they can, and as a result, become more successful in the end. Theoretically, momentum is a principle vehicle of performance that will significantly augment future success and facilitate goal achievement. Consequently, an overall performance consists of occurrences of momentum that vary in frequency and duration. The higher the frequency and the higher the duration, the more likely is success. Research suggests that the main psychological processes that underpin momentum effects are confidence, competence and internal (ability-skill) attributions. Based upon related research, it is hypothesized that PM starts as a conscious process but subsequently becomes a major facilitator of nonconscious automatic execution of human behavior and performance.